Dateline Bangalore: Third World technopolis. - Stremlau, John (Foreign Policy)
Bangalore, India, may offer a preview of a new worldwide labor force that works in cyberspace and operates beyond the reach of government. Many U.S. corporations depend on computer software that has been developed and tailored to their needs in Bangalore and other Indian cities. The engineers in Bangalore are designing the software programs that tell computers what to do. India's yearly software exports have soared since 1990, increasing 53 percent to reach $500 million in the 1994–95 fiscal year. The National Association of Software and Service Companies predicts that sales will reach $5 billion by the end of the decade. The top computer scientists in India have skills that are unsurpassed. The high-tech entry of Bangalore into the global economy is rooted in policy decisions made by the British administration from 1831 until India became independent in 1947, and in the ambitions of New Delhi planners who adopted a policy of autarky until market reforms were introduced in 1991.